The Correlation between Vocabulary Mastery and Reading Comprehension of Students' at the Eleventh Grade of SMA Negeri 1 Palu - Andi Ardini; Mochtar Marhum; Muhammad Arid; Jamiluddin Jamiluddin (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
The ability to understand and evaluate written information is known as reading comprehension, while vocabulary mastery is the ability to use words in a language effectively. This study looked at how reading comprehension and vocabulary mastery relate to one another among eleventh-grade students at SMA Negeri 1 Palu. Out of a total population of 534 students in 15 courses, 73 individuals were chosen at random to participate in a correlational study design. Multiple-choice exams with 30 questions for reading comprehension and 50 items for vocabulary mastery were used to gather data. A linearity test, Spearman's rank correlation, and the Kolmogorov–Smirnov test for normalcy were used to analyse the data because of its non-normal distribution. The findings showed a p-value of 0.135 (p > 0.05), indicating no significant relationship between reading comprehension and vocabulary competence. A very little positive link was shown by the correlation coefficient (rs = 0.177). Therefore, it can be said that in this particular situation, students' reading comprehension ability is not strongly predicted by vocabulary competence alone.